Initial experience with targeted axillary dissection after neoadjuvant therapy in breast cancer patients - Pinto, CS (2022)
Background: Targeted axillary dissection (TAD) combines sentinel node biopsy (SNB) with the removal of the previously marked metastatic node. TAD is a promising concept for axillary restaging in node-positive breast cancer patients with pathological complete response (pCR) to neoadjuvant therapy (NAT). We aimed to evaluate TAD feasibility in this context. Methods: A prospective observational study was conducted in biopsy-confirmed cN1 patients. The removal of the clipped node (CN) was guided by intraoperative ultrasound. SNB used indocyanine green and patent blue V dye. If the CN or sentinel lymph nodes (SLN) had any metastatic foci, or the TAD procedure was unsuccessful, the patient underwent axillary lymph node dissection (ALND). Results: Thirty-seven patients were included. TAD and SNB identification rates were 97.3%. Every retrieved CN was also a SLN. At the individual level, SNB identification rate was 89.2% with indocyanine green and 85.5% with patent blue V dye. The CN identification rate was 81.1%, being higher when the CN was localized on the intraoperative ultrasound (84.4% vs 60.0%). Nodal pCR was achieved by 54.1% of our patients and was more frequent in HER2-positive and triple-negative tumors (p = 0.039). Nineteen patients were spared from ALND. Conclusion: TAD with intraoperative ultrasound-guided excision of the CN and SNB with indocyanine green and patent blue V dye is a feasible concept to identify patients without axillary residual disease after NAT, that can be spared from ALND, although the need for marking the biopsied node should be further investigated. © 2022, The Author(s), under exclusive licence to The Japanese Breast Cancer Society.